Dialectal Variation in Kashubian Stress Placement: An Application of Metrical Theory to Dialectology - Hopkins, Paul (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1992)
If relatedness among languages is best expressed by minor variation in one or more linguistic parameters, so much the more this should be true in the description of the dialects of one language. Yet the stress pattern of the northern Kashubian dialects is apparently quite different from that of the southern dialects. This paper attempts to show that, given an appropriate model for the description of stress, these differences can be seen as ones of degree rather than of kind, with one pattern being a simplified version of the other.